Causes of slowing‐down seasonal CO2 amplitude at Mauna Loa. (20th June 2020) - Wang, Kai; Wang, Yilong; Wang, Xuhui; He, Yue; Li, Xiangyi; Keeling, Ralph F.; Ciais, Philippe; Heimann, Martin; Peng, Shushi; Chevallier, Frédéric; Friedlingstein, Pierre; Sitch, Stephen; et al.
Abstract: Changing amplitude of the seasonal cycle of atmospheric CO2 (SCA) in the northern hemisphere is an emerging carbon cycle property. Mauna Loa (MLO) station (20°N, 156°W), which has the longest continuous northern hemisphere CO2 record, shows an increasing SCA before the 1980s ( p < .01), followed by no significant change thereafter. We analyzed the potential driving factors of SCA slowing‐down, with an ensemble of dynamic global vegetation models (DGVMs) coupled with an atmospheric transport model. We found that slowing‐down of SCA at MLO is primarily explained by response of net biome productivity (NBP) to climate change, and by changes in atmospheric circulations. Through NBP, climate change increases SCA at MLO before the 1980s and decreases it afterwards. The effect of climate change on the slowing‐down of SCA at MLO is mainly exerted by intensified drought stress acting to offset the acceleration driven by CO2 fertilization. This challenges the view that CO2 fertilization is the dominant cause of emergent SCA trends at northern sites south of 40°N. The contribution of agricultural intensification on the deceleration of SCA at MLO was elusive according to land–atmosphere CO2 flux estimated by DGVMs and atmospheric inversions. Our results also show the necessity to adequately account for changing circulation patterns in understanding carbon cycle dynamics observed from atmospheric observations and in using these observations to benchmark DGVMs. Abstract : Amplitude of the seasonal cycle of atmospheric CO2 (SCA) at Mauna Loa (MLO) increased before the mid‐1980s and slowed down thereafter. A skill‐based land–atmospheric model ensemble can robustly reproduce this slowing‐down. Factorial transport experiments further attributed the slowing‐down of SCA at MLO mainly to land carbon cycle response to climate change and atmospheric circulation changes, but not to CO2 fertilization effects and agricultural intensification. Adequate accounting for changing circulation patterns are critical to explore terrestrial carbon cycle dynamics with atmospheric CO2 observations.